Unmet healthcare needs predict frailty onset in the middle-aged and older population in China: A prospective cohort analysis - Jun Li; Di Wu; Haomiao Li; Jiangyun Chen (Frontiers Media S.A., 2023)
ObjectivesOlder populations have a relatively high prevalence of unmet healthcare needs, which can result in poor health status. Moreover, in the coming century, frailty is expected to become one of the most serious global public health challenges. However, there is a lack of clear evidence proving an association between unmet healthcare needs and frailty. This study aimed to assess whether unmet healthcare needs predict the onset of frailty in China.MethodsThe association between frailty and unmet healthcare needs was explored by analyzing data from the China Health and Retirement Longitudinal Study (CHARLS) using random-effects logistic regression and Cox regression with time-varying exposure.ResultsAt baseline, 7,719 respondents were included in the analysis. Random-effects logistic regression shows that unmet outpatient healthcare needs were associated with increased risk of both contemporaneous (adjusted OR [aOR], 1.17; 95% CI, 1.02-1.35) and lagged (aOR, 1.24; 95% CI, 1.05-1.45) frailty, as were unmet inpatient needs (contemporaneous: aOR, 1.28; 95% CI, 1.00-1.64; lagged: aOR, 1.55; 95% CI, 1.17-2.06). For respondents not classified as frail at baseline (n = 5,392), Cox regression with time-varying exposure shows significant associations of both unmet outpatient needs (adjusted HR, 1.23; 95% CI, 1.05-1.44) and unmet inpatient needs (adjusted HR, 1.48; 95% CI, 1.11-1.99) with increased risk of developing frailty.ConclusionsReducing unmet healthcare needs would be a valuable intervention to decrease frailty risk and promote healthy aging in middle-aged and older populations. It is urgent and essential that the equity and accessibility of the medical insurance and health delivery systems be strengthened.